Radiation exposure from diagnostic procedures following allogeneic stem cell transplantation – How much is acceptable?. Issue 5 (July 2014) - Battiwalla, Minoo; Fakhrejahani, Farhad; Jain, Natasha A.; Klotz, Jeffrey K.; Pophali, Priyanka A.; Draper, Debbie; Haggerty, Janice; McIver, Zachariah; Jelinek, James; Chawla, Kamna; Ito, Sawa; Barrett, John
<x content-type="archive" xml:space="preserve">Abstract</x> Background Frequent diagnostic radiology procedures in allogeneic stem cell transplantation (SCT) recipients raise concern about the potential harm from incidental radiation. Objectives To determine the cumulative radiation dose from diagnostic studies in allogeneic SCT and its impact on clinical outcome. Patients and methods This retrospective cohort study was conducted to determine the cumulative radiation dose from diagnostic studies following SCT. Sixty-four consecutive patients with hematological malignancies in a single tertiary care institution underwent total body irradiation (TBI)-based myeloablative conditioning followed by six of six human leukocyte antigen (HLA)-identical sibling allogeneic SCT. The median follow-up was 3 years. The cumulative effective dose in mSv from diagnostic radiological studies in the peri-transplant period from day −30 to day +200 was calculated for each patient and its impact on overall survival and non-relapse mortality was determined. Results The median cumulative radiation exposure from diagnostic radiological procedures was 92 mSv (range 1.2–300), representing about 30× the normal annual background radiation for the population and 10% of the 1200 cGy TBI dose used in conditioning. Sixty-five percent of the cumulative radiation exposure was delivered between day +1 and day 100 and computed tomography scans contributed 88%. In multivariate analysis, diagnostic procedures did not significantly impact clinical outcomes. Conclusions While radiation exposure from diagnostic procedures did not impact clinical outcomes the risk of secondary cancers in long-term survivors is likely to be increased. Our results indicate that patients who are acutely ill for prolonged periods can receive clinically significant radiation doses during their hospital care. Our findings should prompt attempts to limit radiation exposure from diagnostic procedures in post-SCT recipients